The Jews in Poland and Russia. - Polonsky, Antony (Littman library of Jewish civilization (Series), 2019)
In his three-volume history, Antony Polonsky provides a comprehensive survey - socio-political, economic, and religious - of the Jewish communities of eastern Europe from 1350 to the present. Until the Second World War, this was the heartland of the Jewish world: nearly three and a half million Jews lived in Poland alone, while nearly three million more lived in the Soviet Union. Although the majority of the Jews of Europe and the United States, and many of the Jews of Israel, originate from these lands, their history there is not well known. Rather, it is the subject of mythologizing and stereotypes that fail both to bring out the specific features of the Jewish civilization which emerged there and to illustrate what was lost. Jewish life, though often poor materially, was marked by a high degree of spiritual and ideological intensity and creativity. Antony Polonsky recreates this lost world - brutally cut down by the Holocaust and less brutally but still seriously damaged by the Soviet attempt to destroy Jewish culture. Wherever possible, the unfolding of history is illustrated by contemporary Jewish writings to show how Jews felt and reacted to the complex and difficult situations in which they found themselves. This second volume covers the period from 1881 to 1914. It considers the deterioration of the position of the Jews during that period and the new political and cultural movements that developed as a consequence: Zionism, socialism, autonomism, the emergence of modern Hebrew and Yiddish literature, Jewish urbanization, and the rise of popular Jewish culture. Galicia, Prussian Poland, the Kingdom of Poland, and the Tsarist Empire are all treated individually, as are the main towns of these areas. Volume 1 covers the period 1350-1881; Volume 3 covers 1914-2008.